Relationship Between Students’ Learning Style and Their Reading Comprehension - Nurdiana, Nurdiana; Afrizal, Afrizal; Asfira, Rizka (State Islamic University of Sultan Syarif Kasim Riau, 2024)
This research aimed to investigate the correlation between learning style and their reading comprehension The phenomena found by the researchers in the preliminary study were the students have difficulties in comprehending the reading material, making inference, determining the key ideas and locating details, loosing of concentration while reading activity, and bad enable to identify their learning style. This research used quantitative approach. The population of this research was the eight grade students of SMP Negeri 1 Gunung Toar which consists of 30 students. The sample of the research 30 students from population, taken with total sampling technique. In collecting the data, researchers used questionnaire to investigate the students’ learning style and test (multiple choice) for reading comprehension. In analyzing the data, Pearson Product Moment Correlation was used. As the result of the research, they were: Firstly, the researchers found that the mean score of the students’ learning style was 74 which is in high classification where most of the students’ learning style are visual and kinesthetic. Secondly, the mean score of students’ reading comprehension is 41 which is in the low level. Finally, the researchers also found that the significance value of correlation coefficient (r) is 0.524 which is higher than 0.05. In conclusion, there is no significance relationship between students’ learning style and students’ reading comprehension.